Preparation method and application of injectable and reversible-adhesion administration type physical enhanced gelatin hydrogel
By performing a one-step Michael addition reaction on gelatin, the NBNAGA group is grafted and the photosensitive bisamide monomer is formed. UV light is used to induce the formation of a completely physically crosslinked hydrogel, which solves the problems of chemical crosslinking stability and hydrophilicity limitation of hydrogels in the prior art, and achieves the effects of injectable, adhesion reversible and hydrophobic drug loading.
Patent Information
- Application Number
- CN202510330164.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-20
- Publication Date
- 2025-04-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The chemical crosslinking stability of existing methacrylamide modified gelatin hydrogels limits its application, and the absolute hydrophilicity limits the hydrophobic drug loading capacity.
Through a one-step Michael addition reaction, the N'-(2-nitrobenzyl)-N-acryloylglycine (NBNAGA) group is grafted onto gelatin to form a photosensitive bisamide monomer, and the formation of a completely physically crosslinked hydrogel is induced by ultraviolet light to achieve injectable, adhesion reversible and hydrophobic drug loading.
The thermally induced gel-sol transformation, reversible adhesion, self-healing and other properties of hydrogels have been achieved, and has shown great application potential in the field of biomedical materials.
Smart Images

Figure CN119842101A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomedical materials, in particular to a preparation method and application of an injectable, reversibly adherent, drug-delivery-type physically enhanced gelatin hydrogel. Background Art
[0002] Gelatin is a partially hydrolyzed protein extracted from collagen. Gelatin is soluble in warm water and can form a transparent gel after cooling due to the triple helix hydrogen bonding of collagen. Due to its similarity to the extracellular matrix and good biocompatibility with the human body, it is widely used as a cell growth matrix, drug-specific carrier, and scaffold material in tissue engineering applications. Nowadays, stabilization or functionalization of gelatin has become a research hotspot. Methacrylamide-modified gelatin is a hydrogel material that is photoinduced cross-linked after double bond modification of gelatin with methacrylic anhydride. It has unique advantages such as good biocompatibility, low cost, and stable chemical properties. However, due to the stability of chemical cross-linking, the rigidity and firmness of the material limit its application under specific conditions such as separation and degradation; and the absolute hydrophilicity also limits the hydrophobic drug loading capacity of the hydrogel. Based on this, a preparation method and application of an injectable, adhesion-reversible drug delivery-type physically enhanced gelatin hydrogel are proposed. Summary of the invention
[0003] In view of the deficiencies in the prior art, the present invention provides a method for preparing and applying an injectable, reversibly adherent, drug-delivery-type physically enhanced gelatin hydrogel. The obtained hydrogel shows good application potential in the field of biomedical materials.
[0004] To achieve the above object, the present invention provides the following technical solution: a method for preparing an injectable, reversibly adherent, drug-delivery-type physically enhanced gelatin hydrogel, comprising the following steps: (1) Weigh N' -(2-Nitrobenzyl)- N -Acryloylglycinamide ( NB NAGA) and dimethyl sulfoxide (DMSO) were dissolved in a light-proof environment to obtain a pre-use solution; (2) Weigh gelatin and ultrapure water to dissolve. After complete dissolution, adjust the pH to 9 with saturated sodium bicarbonate (NaHCO3) solution, continue to add ultrapure water and stir thoroughly to obtain a gelatin aqueous solution; (3) In a light-proof environment, slowly drop the pre-used solution into the gelatin aqueous solution for reaction. Place the solution after the reaction into an activated dialysis bag for dialysis. After the dialysis is completed, freeze-dry the solution to obtain a white foamy substance (GN). (4) In a light-proof environment, weigh the white foamy substance and dissolve it in PBS buffer solution. After it is completely dissolved, transfer the resulting precursor solution (GN solution) into a mold and treat it with ultraviolet light to obtain an injectable, reversibly adhesive drug-delivery gelatin hydrogel.
[0005] Preferably, in step (1), N' -(2-Nitrobenzyl)- N -The solid-liquid ratio of acrylyl glycinamide and dimethyl sulfoxide is (4-50): 1 mg / mL; the dissolution temperature is 50°C.
[0006] Preferably, in steps (1)-(2), N' -(2-Nitrobenzyl)- N -The mass ratio of acrylyl glycinamide to gelatin is (0.04-0.5): 1 g / g.
[0007] Preferably, in step (2), the solid-liquid ratio of gelatin to the total amount of ultrapure water is 1:19 g / mL; the dissolution temperature is 50° C.; and the stirring time is 2 h.
[0008] Preferably, in step (3), the reaction temperature is 50°C, the reaction time is 24 hours, the dialysis time is 72 hours, the freeze-drying time is 24 hours, and the storage temperature of the white foamy substance is -20°C.
[0009] Preferably, in step (3), the dialysis bag is a MWCO 3500 dialysis bag.
[0010] Preferably, in step (4), the concentration of the precursor solution is 10% w / v; and the dissolution temperature is 40°C.
[0011] Preferably, in step (4), the ultraviolet irradiation treatment is performed using a 365 nm ultraviolet lamp at 30 mW / cm 2 Irradiate with the radiation intensity for 5 min.
[0012] In another technical solution, a method is provided for using the above-mentioned injectable, reversibly adhered, drug-delivery-type physically enhanced gelatin hydrogel in a hydrophobic drug sustained-release carrier.
[0013] The present invention provides a preparation method and application of an injectable, reversibly adherent drug-delivery type physically enhanced gelatin hydrogel, which has the following beneficial effects compared with the prior art: The present invention successfully utilizes the amide group on the lysine residue to NB The olefin on the NAGA monomer undergoes a one-step Michael addition reaction to convert the photosensitive bisamide monomer into NBNAGA is grafted onto natural gelatin without the addition of initiators, and low-concentration GN aqueous solutions can form physically reinforced hydrogels with certain mechanical strength within tens of seconds under ultraviolet light irradiation. This fully physically cross-linked network system gives the hydrogels thermally induced gel-sol transition, reversible adhesion, self-healing and other properties; in addition, the photoresponsive hydrophobic groups o-NB It can load the hydrophobic drug curcumin and successfully release the drug under ultraviolet light. After the first-stage release of curcumin, the second-stage release of curcumin can be achieved by heating. It also has good biocompatibility and shows great application potential in the field of biomedical materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings: Figure 1 Figure 1 is a graph showing the characterization of GN in the present invention: (a) degree of substitution of different GNs; (b) gelatin, NB NAGA, GN 1 H NMR; (c) FT-IR spectrum; (d) irradiation at 365 nm (30 mW / cm 2 ) recorded under 400 nm. The inner figure shows the equilibrium time of different GN.
[0015] Figure 2 The figures are related to the mechanical characteristics of the GN hydrogels of the present invention: (a) the gel point of different GN hydrogels, the inner figure is a typical kinetic curve formed by the dynamic time scanning rheological curve of GN-5 hydrogel; (b) the final storage modulus G′ of different GN hydrogels after storage at 4°C for 24 h; (c) the compressive stress-strain curves of different GN hydrogels after storage at 4°C for 24 h.
[0016] Figure 3 The graphs showing the correlation between the microporous structure, swelling property and degradation ability of the GN hydrogel of the present invention are as follows: (a) SEM images of different GN hydrogels in PBS; (b) pore size; (c) swelling; (d) degradation.
[0017] Figure 4 Graphs related to the adhesive properties of the GN hydrogel of the present invention: (a) shear strength of GN hydrogel and fibrin glue; (b) adhesive strength; (c) peel strength; (d) bursting pressure; (e) schematic diagram of the experimental setup for conducting lap shear, wound closure, peeling and bursting pressure studies with pig skin as the target site.
[0018] Figure 5Temperature dependence correlation diagram of GN hydrogel of the present invention: (a) Changes of G′ and G″ of different GN hydrogels under temperature scanning from 25°C to 100°C; (b) Frequency scanning measurement of GN-5 hydrogel at 25°C and 80°C, and photos are also shown; (c) Adhesion strength of GN-5 hydrogel at different temperatures; (d) Continuous cycle adhesion test of GN-5 hydrogel.
[0019] Figure 6 The self-healing and injection characteristics of the GN-5 hydrogel of the present invention are related to the following diagrams: (a) strain scanning measurement of the GN-5 hydrogel; (b) dynamic strain step test; (c) shear thinning test; (d) macroscopic self-healing process image, the GN-5 hydrogel was cut into two pieces, stained first, and then contacted again for 20 minutes to recover; (e) stress-strain curves of the hydrogel before damage and after recovery: (f) The precursor solution sample was injected into deionized water at 25°C.
[0020] Figure 7 The biocompatibility and curcumin release correlation diagrams of the GN hydrogel of the present invention are as follows: (a) optical density of L929 cells incubated with CCK-8 kit at 450 nm wavelength on days 1, 3 and 5 of different hydrogels; (b) relative cell viability; (c) DEE of different GN hydrogels on curcumin; (d) DLC of different GN hydrogels on curcumin; (e) in vitro curcumin release curves of different GN hydrogels at 37°C; (f) curcumin release curves of GN-5 hydrogel at different temperatures.
[0021] Figure 8 The figures are related to the fitting results of different kinetic models of the present invention for the curcumin release process of GN hydrogel at 37°C: (a) zero-order kinetic model; (b) first-order kinetic model; (c) Higuchi model: (d) Ritger-Peppas model; (e) the fitting results of the Ritger-Peppas model for the curcumin release process of GN-5 hydrogel at 37°C, 45°C and 60°C. DETAILED DESCRIPTION
[0022] The following examples are used to explain the implementation methods of the present application in detail, so that the implementation process of how the present application uses technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly.
[0023] Example 1 A method for preparing an injectable, reversibly adherent drug-delivery gelatin hydrogel comprises the following steps: (1) Weigh 10 mg N' -(2-Nitrobenzyl)- N -Acryloylglycinamide ( NBNAGA) and 10 mL of dimethyl sulfoxide (DMSO) were dissolved at 50 °C for 2 h in a light-proof environment to obtain a pre-use solution; (2) Weigh 1 g of gelatin and 10 mL of ultrapure water and dissolve them at 50 °C for 2 h. After complete dissolution, adjust the pH to 9 with 1 mL of saturated sodium bicarbonate solution (NaHCO3 solution). Continue to add 9 mL of ultrapure water and stir thoroughly for 15 min to obtain a gelatin aqueous solution. (3) In a light-proof environment, slowly add the pre-used solution to the gelatin aqueous solution and react at 50°C for 24 hours. Place the reacted solution into an activated dialysis bag (MWCO 3500) and dialyze for 72 hours to remove the ungrafted N' -(2-Nitrobenzyl)- N -Acryloyl glycinamide monomer ( NB NAGA monomer) and dimethyl sulfoxide (DMSO), and then freeze-dried for 24 h after dialysis to obtain a white foamy substance (GN), which was stored at -20 °C.
[0024] (4) Under light-proof environment, weigh the white foamy substance (GN) and PBS buffer solution, dissolve them at 40°C for 2 h, and after complete dissolution, transfer the resulting 10% w / v precursor solution (GN solution) into a polytetrafluoroethylene mold and illuminate it with a 365 nm UV lamp at 30 mW / cm 2 After irradiation with an intensity of 500 nm for 5 min, the hydrogel failed to gel (denoted as GN-1 hydrogel).
[0025] The amino content of GN (denoted as GN-1) in this example was determined by 2,4,6-trinitrobenzenesulfonic acid (TNBS) assay, and the degree of substitution (DS) of GN-1 was calculated to be 6.6±1.1%.
[0026] Example 2 A method for preparing an injectable, reversibly adherent drug-delivery gelatin hydrogel is substantially the same as that of Example 1, except that: NB The dosage of NAGA was 40 mg; the prepared injectable, reversibly adhesive drug-delivery gelatin hydrogel (denoted as GN-2 hydrogel) was obtained.
[0027] The amino content of GN (denoted as GN-2) in this example was determined by 2,4,6-trinitrobenzenesulfonic acid (TNBS) assay, and the degree of substitution (DS) of GN-2 was calculated to be 11.2±1.6%.
[0028] Example 3 A method for preparing an injectable, reversibly adherent drug-delivery gelatin hydrogel is substantially the same as that of Example 1, except that: NBThe dosage of NAGA was 47 mg; the prepared injectable, reversibly adhesive drug-delivery gelatin hydrogel (denoted as GN-3 hydrogel) was obtained.
[0029] The amino content of GN (denoted as GN-3) in this example was determined by 2,4,6-trinitrobenzenesulfonic acid (TNBS) assay, and the degree of substitution (DS) of GN-3 was calculated to be 16.4±0.6%.
[0030] Example 4 A method for preparing an injectable, reversibly adherent drug-delivery gelatin hydrogel is substantially the same as that of Example 1, except that: NB The dosage of NAGA was 75 mg, and the prepared injectable, reversibly adhesive drug-delivery gelatin hydrogel (denoted as GN-4 hydrogel) was obtained.
[0031] The amino content of GN (denoted as GN-4) in this example was determined by 2,4,6-trinitrobenzenesulfonic acid (TNBS) assay, and the degree of substitution (DS) of GN-4 was calculated to be 25.7±0.5%.
[0032] Example 5 A method for preparing an injectable, reversibly adherent drug-delivery gelatin hydrogel is substantially the same as that of Example 1, except that: NB The dosage of NAGA was 100 mg, and the prepared injectable, reversibly adhesive drug-delivery gelatin hydrogel (denoted as GN-5 hydrogel) was obtained.
[0033] The amino content of GN (denoted as GN-5) in this example was determined by 2,4,6-trinitrobenzenesulfonic acid (TNBS) assay, and the degree of substitution (DS) of GN-5 was calculated to be 41.2±1.3%.
[0034] Example 6 A method for preparing an injectable, reversibly adherent drug-delivery gelatin hydrogel is substantially the same as that of Example 1, except that: NB The dosage of NAGA was 200 mg, and the prepared injectable, reversibly adhesive drug-delivery gelatin hydrogel (denoted as GN-6 hydrogel) was obtained.
[0035] The amino content of GN (denoted as GN-6) in this example was determined by 2,4,6-trinitrobenzenesulfonic acid (TNBS) determination method, and the degree of substitution (DS) of GN-6 was calculated to be 54.8±0.7%.
[0036] Example 7 A method for preparing an injectable, reversibly adherent drug-delivery gelatin hydrogel is substantially the same as that of Example 1, except that: NBThe dosage of NAGA was 300 mg, and the prepared injectable, reversibly adhesive drug-delivery gelatin hydrogel (denoted as GN-7 hydrogel) was obtained.
[0037] The amino content of GN (denoted as GN-7) in this example was determined by 2,4,6-trinitrobenzenesulfonic acid (TNBS) assay, and the degree of substitution (DS) of GN-7 was calculated to be 68.6±0.5%.
[0038] Example 8 A method for preparing an injectable, reversibly adherent drug-delivery gelatin hydrogel is substantially the same as that of Example 1, except that: NB The dosage of NAGA was 500 mg, and the prepared injectable, reversibly adhesive drug-delivery gelatin hydrogel (denoted as GN-8 hydrogel) was obtained.
[0039] The amino content of GN (denoted as GN-8) in this example was determined by 2,4,6-trinitrobenzenesulfonic acid (TNBS) assay, and the degree of substitution (DS) of GN-8 was calculated to be 77.4±2.2%.
[0040] Synthesis and characterization of GN and preparation of GN hydrogel The present invention uses a one-step Michael addition reaction to NB The NAGA group was grafted onto the terminal amino group of lysine in the gelatin side chain, and the functional derivative GN of natural gelatin macromolecule was successfully prepared. The amino group concentration (AC) of 8 GN (GN-1 / 2 / 3 / 4 / 5 / 6 / 7 / 8) and raw gelatin was determined according to the 2,4,6-trinitrobenzenesulfonic acid (TNBS) method. The amino group concentration (AC) was converted from the ultraviolet absorbance value at a wavelength of 346nm. Figure 1 a shows the DS values of 8 modified gelatins, ranging from 6.6±1.1% to 77.4±2.2%. The DS value was calculated according to the following formula: ; For raw materials gelatin, NB NAGA and GN conducted nuclear magnetic resonance hydrogen spectrum tests. Figure 1 As shown in b. NB NAGA's H-NMR spectrum ( Figure 1 b) shows obvious chemical shifts at 7.6, 7.8 and 8.1 ppm, which confirms the presence of aromatic protons. Comparison of the spectra of GN-5 and raw gelatin ( Figure 1 b middle and bottom), the additional peaks at about 7.6, 7.8 and 8.1 ppm on GN-5 and the lysine methylene proton peak at 2.9 ppm are significantly decreased compared with those on gelatin, indicating that the raw gelatin was successfully modified by Michael addition reaction.
[0041] Likewise, Fourier transform infrared spectroscopy tests were also performed. Figure 1 The spectrum on c clearly shows that at 1524 cm -1 There is an obvious peak around , which corresponds to the functional NB The characteristic peak of the -NO2 group of NAGA monomer. Comparing the spectra of raw gelatin and modified GN, no obvious difference was observed. This is because NB NAGA monomer is grafted onto the terminal amino group of lysine in the side chain of gelatin, while the lysine content in the commercial type A gelatin used is very low, accounting for about 2.76% of the total gelatin content.
[0042] In order to verify the photolysis performance, GN solutions with different substitution degrees (0.3% w / v) were prepared using PBS solution as solvent. 2 ) UV light was used to irradiate the solution, and the UV-visible absorption spectra of each GN solution were tested at 0, 0.5, 1, 1.5, 2, 3, 5, 10, and 15 min, respectively. Figure 1 d depicts the UV-visible absorption spectra of GN-5 solution at different irradiation times. The characteristic absorption maximum at 270 nm gradually decreases, while the characteristic absorption maximum at 340 nm increases with the extension of irradiation time. 2 Under ultraviolet light irradiation, the absorbance is basically stable within about 2 minutes, indicating that the light-induced reaction is basically completed. Figure 1 The figure in d depicts the UV photolysis equilibrium time of different GN solutions. The higher the DS, the faster the equilibrium. For example, the equilibrium time of GN-1 is 200.7±4.1s (DS is 6.6±1.1%), while the equilibrium time of GN-8 is 42.1±3.0s (DS is 77.4±2.2%). This is because GN-8 can release o-NB The higher the concentration of the group, the easier the UV-induced dissociation. The UV-induced dissociation equilibrium time of GN-3 (DS is 16.4±0.6%) is longer, which is 171.7±4.1s. This may be due to the lack of double bond substituents on the gelatin side chains in GN, which weakens the non-covalent relationship between the molecular chains. According to the photolysis equilibrium time of each GN, in the following tests, UV irradiation for 5min was uniformly selected to prepare GN hydrogels.
[0043] Given that the lysine content in gelatin is very low, NB The molecular weight of NAGA is much smaller than that of gelatin, so the molecular weight of GN does not change much after modification, so the concentration of 10% w / v is still selected to prepare the precursor solution of all GN hydrogels. Then, 365nm ultraviolet light is used for in-situ irradiation, and the hydrogel can be formed within tens of seconds. The reason is that ultraviolet light can quickly induce the photoresponsive groups in the GN precursor solution. o-NB The group undergoes a photolysis removal reaction. At this time, the "uncaged" diamide group forms double hydrogen bonds and single hydrogen bonds between or within the chain, and further rearranges the original helical structure of gelatin, greatly enhancing the interchain interaction. In this way, through a mild chemical modification and a convenient UV cross-linking operation, a gelatin-based hydrogel completely enhanced by physical effects is constructed. Of course, GN-1 with a lower degree of substitution (DS) (DS is 6.6±1.1%) cannot achieve UV-induced gelation due to insufficient physical enhancement of the chain action.
[0044] Performance Testing 1. Rheological and mechanical properties testing A rotational rheometer (AntonPaar MCR 302e) was used to measure the rheological properties of GN solutions and GN hydrogels. The samples for the dynamic time sweep test and viscosity test were GN solutions (10% w / v), and the samples for the other rheological tests were GN hydrogels. The dynamic time sweep test was performed at 25 °C in parallel plate mode (25 mm diameter) under UV light (365 nm, 30 mW / cm 2 ), 1% strain, 1 Hz frequency and 0.5 mm gap. Viscosity tests were performed at 25 °C, parallel plate mode (25 mm diameter), shear rates from 1 to 500 s −1 The test conditions were carried out under logarithmic change conditions. The test conditions of the frequency sweep test were 25°C, shear mode, 1% strain, angular frequency 0.1-100rad / s and 0.5mm gap. The frequency sweep test of GN-5 at 80°C was the same as the frequency sweep test at 25°C except for the temperature. The test conditions of the temperature sweep test were 25-100°C (2°C / min), shear mode, 1% strain, 1Hz frequency and 0.5mm gap. The test conditions of the critical strain point were measured by a strain amplitude sweep test (1%-1000%) at a temperature of 25°C and a constant frequency of 10rad / s. The self-healing properties of GN hydrogel were carried out in an alternating step strain sweep test of 1%-800%-1% strain.
[0045] An electronic universal testing machine (CMT6103, China) was used to measure the compression properties of GN hydrogels. A cylindrical sample (5 mm in height × 5 mm in diameter) was placed on a compression measurement plate and subjected to compression testing at a speed of 1 mm / min using an electronic universal testing machine equipped with a 1000 N load cell.
[0046] Test results: Under UV light irradiation, dynamic time scanning rheology experiments were carried out on all GN precursor solutions. Figure 2The figure in a shows the formation kinetics of GN-5 hydrogel. As time goes by, the storage modulus G′ increases sharply and quickly exceeds the dissipation modulus G″. The gel time of the GN solution is determined by the intersection of the two curves. Except for GN-1, all GN hydrogels (10% w / v) are formed within tens of seconds. Since GN-1 has the lowest degree of substitution (DS), which is only 6.6±1.1%, the degree of physical crosslinking after UV irradiation is the lowest and is not enough to induce gelation. However, the gel points of other GN hydrogels also vary greatly, ranging from 59.2±1.7s for GN-2 to 11.7±1.7s for GN-8 ( Figure 2 a). In gelatin NB The more NAGA groups are substituted, the faster the gelation speed of GN is. In addition, the GN-5 hydrogel reaches equilibrium in about 100 s, which is roughly consistent with the change time in the UV absorbance test. The same is true for other GN hydrogels, but there are differences in equilibrium time. The higher the degree of substitution (DS), the shorter the equilibrium time.
[0047] After continuing to observe the gel point, G′ is several orders of magnitude higher than G″, which indicates that the GN-5 hydrogel has high strength. At the same time, the helical structure and segment aggregation growth brought by the cross-linking density can continue to increase the rigidity of the hydrogel. It is well known that the rheological properties of gelatin-based hydrogels can be controlled by a variety of parameters, such as polymer concentration, degree of substitution, UV irradiation, storage time, etc. Therefore, each GN precursor solution was uniformly stored at 4°C for 24 hours after UV irradiation for 5 minutes, and then a frequency sweep test was performed to reflect the strength of the hydrogel with the final storage modulus G′ ( Figure 2 b). The final G′ of GN-5 hydrogel is 3152±68Pa, which is the toughest hydrogel compared with other GN hydrogels, indicating that the mechanical properties of GN hydrogels are not completely affected by NB The influence of NAGA content. NB At higher NAGA contents, the enhancement of hydrogen bonding is apparently due to the large number of diamide groups o-NB The release of photolysis, but at the same time, the amidation of the lysine terminal groups in gelatin will also damage the double helix structure of gelatin itself. The reason why GN-5 has better mechanical strength than other GNs may be due to the optimal adaptation of the two aspects.
[0048] The compressive properties were evaluated by compressive strain measurements (see Figure 2 c). Consistent with the above results, GN-5 hydrogel exhibited the highest compressive strength (about 800 kPa at a strain of 82%), which is about 40 times that of GN-8 hydrogel and 30 times that of GN-2 hydrogel. Of course, there was a slight decrease in compressive strain at the same time, which may be due to the dense entanglement between the NAGA network and the helical network.
[0049] 2. Scanning Electron Microscope (SEM) The microstructure of GN hydrogel was obtained on a TESCANMIRA scanning electron microscope. The GN hydrogel in each example was stored at 4°C for 24 hours. After that, it was placed in a freeze dryer and freeze-dried to completely remove the residual solution. Then, metal particles were plated on the surface of the sample using a metal sputtering device, and the microscopic morphology of the gel was observed on a scanning electron microscope. The pore size of the GN hydrogel was obtained by averaging at least 3 images of 3 samples under each condition using ImageJ software (n=5).
[0050] Test results: Scanning electron microscopy tests showed the detailed structure of GN hydrogel at the microscopic scale. Figure 3 a shows that all GN hydrogels exhibit a uniform three-dimensional porous structure. The average pore size of GN hydrogels with different NBNAGA contents ranges from 14.3±3.8 to 88.5±7.3 μm ( Figure 3 b). Regardless of whether the degree of substitution is low or high, the GN hydrogel does not have the most compact structure. Consistent with the mechanical results, the GN-5 hydrogel has the most compact structure and the smallest pores (DS≈41.2±1.3%). This indicates that the optimal degree of substitution range is between 40-50%.
[0051] 3. In vitro swelling rate (SR) and degradation rate The GN hydrogel in each example was stored at 4°C for 24 h and then freeze-dried to obtain its dry weight W d The freeze-dried GN hydrogel samples were placed in a PBS solution at 37°C and incubated for 8 h. The samples were carefully taken out from the solution at regular intervals, the surface moisture was gently wiped off, and the mass change of each GN hydrogel was recorded to obtain Ws. The swelling rate SR of the GN hydrogel was calculated according to the following formula: ; The GN hydrogels in each example were stored at 4°C for 24 hours and then freeze-dried to obtain their initial dry weight. Each freeze-dried GN hydrogel sample was placed in a 24-well plate containing 2 mL of PBS solution and incubated at 37°C for 3 weeks. The PBS solution was replaced every 3 days, and the incubated samples were freeze-dried and weighed on days 1, 7, 14, and 21 (n=5), and the in vitro degradation rate was finally obtained.
[0052] Test results: The hydrogels were incubated in PBS solution at 37°C for 8 h, and the mass changes of different hydrogels were recorded. SR ( Figure 3c). Consistent with the trend of mechanical and SEM measurements, the SR value of GN-5 hydrogel is the smallest, about 16.4±0.4g / g. The swelling property of hydrogel reflects its structural stability during long-term use in physiological environment. Here, GN-5 shows good anti-deformation ability. The SR of GN-2 and GN-8 hydrogels with relatively large pore sizes are larger, 30.6±0.3g / g and 20.1±0.3g / g, respectively.
[0053] Figure 3 d shows the in vitro degradation of GN hydrogels with different substitution degrees in PBS solution at 37°C. The 7 GN hydrogels were freeze-dried and weighed on days 1, 7, 14, and 21. From the results, all 7 GN hydrogels showed good degradation. Among them, for GN-5 hydrogel, the degradation ratio on day 7 was 62.5±2.0%. The degradation ratio increased to 87.4±4.1% on day 14, and the degradation ratio was 95.1±2.4% on day 21, which was almost completely degraded.
[0054] 4. Adhesion performance test (1) Preparation of adhesion samples: Purchase fresh pig skin, cut the pig skin into 1.5×5 cm strips, soak it in PBS solution at 37°C for 1 hour, and then remove the fat on the inner surface of the pig skin. Prepare the GN solution in each example.
[0055] (2) Overlap shear test: 200 μL of GN solution was dripped into the designated area on the inner surface of one of the pigskins, and then one end of the other pigskin was gently placed on the end of the pigskin coated with GN solution to form an overlapping area of 3×1.5 cm, and then irradiated with ultraviolet light to form a hydrogel. Then, a pressure of 500 g was applied for 20 min to enhance the adhesion. After storage at 4°C for 24 h, the test was performed at room temperature of 25°C.
[0056] (3) Tensile test: 200 μL of GN solution was injected into the bonding area (1.5×0.3 cm) at both ends of two pigskins and irradiated with UV light to form a hydrogel. After being stored at 4°C for 24 h, the samples were tested at room temperature (25°C). In order to evaluate its temperature sensitivity, the pigskin samples bonded with GN-5 solution after being stored at 4°C for 24 h were placed at 35°C, 45°C, and 55°C for 0.5 h and then tested immediately. In order to further explore the temperature-induced reversibility of adhesion, 500 μL of GN-5 solution was injected into the bonding area (15×3.0 mm) at both ends of two pigskins and irradiated with UV light to form a hydrogel. After being stored at 4°C for 24 h, they were stored at 25°C for 0.5 h, and then the samples were immediately taken out for testing. After the test, the GN-5 hydrogel was dissolved by heating to 55°C and then re-bonded. Pressure was applied to the re-bonded area to make the two bonding areas of the pig skins in close contact. After being stored at 4°C for 24 hours, they were further stored at 25°C and 55°C for 0.5 hours before being tested again. This process was repeated 5 times.
[0057] (4) Peel-off adhesion test: 200 μL of GN solution was injected into the inner surface of pigskin (4×1.5 cm), and then another inner surface of pigskin was covered on top and irradiated with UV light. The test was performed after storage at 4°C for 24 h.
[0058] (5) Burst pressure experiment: Cut a piece of pig skin of 2×2 cm, cut a circular notch with a diameter of 2 mm on the surface of the pig skin, and fix the pig skin in a measuring device connected to a syringe filled with PBS solution and a pressure gauge. Inject about 200 μL of GN solution into the circular notch of the pig skin, and then irradiate with ultraviolet light for 5 minutes. The thickness of the formed hydrogel is about 3 mm. Set the injection rate of the injection pump to 10 mL / min, start injecting PBS solution into the device and apply pressure to the circular notch covered by the hydrogel. The pressure gauge is used to measure the burst pressure value of the hydrogel, and the peak pressure is identified as the burst pressure.
[0059] All measurements were performed with fibrin glue (Shanghai RAAS Blood Products Co., Ltd.) as a control, and the experimental tests were repeated three times.
[0060] Test results: In order to determine the adhesive ability of the physically enhanced modified gelatin hydrogel, four tests were conducted: lap shear test, tensile test, peel test and burst pressure test. The first three tests were conducted according to the standardized test methods specified by the American Society for Testing and Materials (ASTM) on a uniaxial tensile testing machine, and the last test was conducted using a published method ( Figure 4e, Publication 1: Hong Y, Zhou F, Hua Y, Zhang X, Ni C, Pan D, Zhang Y, Jiang D, Yang L, Lin Q, Zou Y, Yu D, Arnot DE, Zou X, Zhu L, Zhang S, OuyangH (2019) A strongly adhesive hemostatic hydrogel for the repair of arterialand heart bleeds. Nat Commun 10(1):2060.) was completed on a homemade device. In addition, the shear strength of each GN hydrogel was calculated according to the ASTM F2255-05 standard. Figure 4 As shown in a, among the GN hydrogels with different degrees of substitution, GN-5 hydrogel has the best adhesive properties, with a maximum shear strength of 21.5±0.3 kPa, which is higher than fibrin glue (17.5±0.5 kPa). In addition, the shear strength of GN-5 hydrogel is about 3 times that of GN-8 hydrogel and nearly 7 times that of GN-2 hydrogel, which indicates that NB The content of NAGA has a nonlinear effect on the adhesive properties. The reason why the adhesive strength of GN-2 hydrogel is weak is that NB The relatively low NAGA content resulted in insignificant improvement in hydrogen bonding on the pigskin surface. NB The NAGA content was high, but their adhesion was also weak, which was most likely due to the microscopic phase separation of the hydrogel during the rapid phase transition, thereby reducing its shear strength.
[0061] Next, the adhesion strength of GN hydrogels with different DS was tested using pig skin tissue as a model. The adhesion strength of GN-5 hydrogel was 106.4±4.1 kPa, which was much greater than that of fibrin glue (28.3±0.7 kPa). Figure 4 b). The adhesion strengths of GN-6 and GN-7 hydrogels were 41.1 ± 1.8 kPa and 31.1 ± 1.7 kPa, respectively, which were also higher than that of fibrin glue, indicating that GN hydrogels have advantages in improving adhesion.
[0062] Figure 4 c shows the test results of the peel strength of GN hydrogel. Among all GN hydrogels, the peel strength of GN-5 reached 20.2±0.4N / m. In addition, GN hydrogel has excellent properties such as low cost advantage and good biocompatibility.
[0063] As the main test for evaluating the pressure resistance of hydrogels, a burst pressure test was conducted in a test device constructed according to the guidance of Publication 1. The schematic diagram of the device is shown in Figure 4 e. The bursting pressure test device was used to obtain the bursting pressure data of GN gels with different substitution degrees. These data are shown in Figure 4 d. It can be found that the burst pressure of GN-5 hydrogel reaches 141±6 mmHg, which is higher than 52±1 mmHg of fibrin glue and normal systolic blood pressure (120 mmHg). This result indicates that GN-5 hydrogel has broad application potential as a hemostatic sealant.
[0064] 5. Cell culture and cytotoxicity assay The biocompatibility of GN hydrogel was studied using mouse fibroblast L929 as a model. The GN hydrogels (experimental group) and the control group (without GN hydrogel, other conditions were the same as the experimental group) in each example were co-incubated with L929 fibroblasts. L929 cells were cultured in Dulbecco's modified medium (DMEM) containing 10% fetal bovine serum and 100U / mL penicillin / streptomycin. In the cytotoxicity experiment, L929 cells were cultured at 4×10 6 The density of 100 / mL was added into a 96-well plate, and the extracts of each gelatin hydrogel and the control group were incubated.
[0065] After incubation for a certain period of time, CCK-8 reagent was added to the 96-well plate and cultured in an incubator at 37°C and 5% CO2 for 2 h. Cell viability was measured at a wavelength of 450 nm using a multi-mode microplate reader.
[0066] Test results: Good biocompatibility is an indispensable property of hemostatic adhesives. To evaluate the cell compatibility of different hydrogels, each GN hydrogel and the control group (without hydrogel) were incubated with L929 fibroblasts. Figure 6 As shown in a, the OD values of different GN groups increased with the increase of mixing time. Calculation showed that after 1, 3 and 5 days of incubation, the relative cell viability of GN-2 hydrogel was 99.5±3.6%, 99.1±3.4% and 98.4±1.7%, respectively, with almost no cytotoxicity. The figure also shows the relevant values of GN-5 hydrogel, which were 77.4±6.2%, 75.0±6.6% and 71.5±3.4% ( Figure 7 b). GN-5 hydrogel showed slight toxicity. NB The NAGA content in GN hydrogels was more significant, and the most likely reason was the toxicity of the substituted groups and the photoinduced nitroso byproducts. But overall, GN hydrogels have satisfactory biocompatibility and will hardly hinder in vivo biological applications.
[0067] 6. Loading and release of curcumin Because of the hydrophobicity of curcumin, the co-solvent self-assembly method was selected to encapsulate it into GN hydrogel. First, 0.2g GN was dissolved in 50mL PBS solution, stirred and dissolved at 500rpm in a 40℃ water bath for 2h, and 5mL DMSO solution containing 0.025g curcumin was slowly added at a rate of 0.1mL / min after complete dissolution. After the addition was completed, stirring was continued for 24h. After 24h, the reacted solution was placed in a pre-activated dialysis bag (MWCO 3500) and dialyzed for 72h. Deionized water was replaced approximately every 6h to completely remove the organic solvent and unloaded curcumin. After the final dialysate was freeze-dried, a yellow foam substance was obtained, which was Cur@GN. The absorbance of Cur@GN in DMSO / PBS solution at a wavelength of 420nm was measured, and the loading amount of curcumin was obtained according to the curcumin standard calibration curve. The drug encapsulation efficiency (DEE%) and drug loading rate (DLC%) were calculated as follows: ; Among them, W Cur is the total amount of drug initially added, W Cur-loaded is the mass of curcumin loaded on GN, W GN is the weight of GN.
[0068] In the curcumin release study, 0.02 g of Cur@GN was weighed and added to 0.2 mL of PBS solution (10% w / v), dissolved at 40 °C, and injected into a cylindrical polytetrafluoroethylene mold (Φ10×2 mm) after complete dissolution. 2 ) for 5 minutes to make it gel, and then put it into 3mL PBS solution and shake it at a constant temperature of 37℃. UV test was carried out at the selected time point, and the concentration of curcumin in the solution was obtained according to the UV absorbance at a wavelength of 420nm. In addition, comparative experiments were carried out at 45℃ and 60℃ respectively.
[0069] Test results: In NAGA, the photosensitive and hydrophobic o-NB groups around the diamide structure can serve as assembly domains for hydrophobic drugs. Figure 7As shown in c and d, curcumin was used as a model drug to determine the drug encapsulation efficiency (DEE%) and drug loading rate (DLC%) of GN hydrogel for curcumin. Based on the absorbance-concentration standard curve of curcumin, it was calculated that the DEE% of different Cur@GN hydrogels ranged from 10.62±0.56% to 25.62±0.85%. GN-5 hydrogel was the best among all hydrogels and had the strongest encapsulation ability. In addition, the DLC% of Cur@GN-5 also ranked first among the GN series of hydrogels at 4.57±0.14%. Lower NB The NAGA content leads to a lack of hydrophobic loading sites, which in turn leads to lower encapsulation and loading rates. NB The NAGA group may hinder the loading of hydrophobic drugs due to steric hindrance. The GN-5 polymer with the best degree of substitution is most favorable for drug loading.
[0070] like Figure 7 As shown in e, the release behaviors of seven Cur@GN hydrogels were systematically studied at 37°C. Under the induction of ultraviolet light, o-NB The groups decomposed, which promoted the excretion of curcumin from the gel. GN-2 hydrogel showed the highest drug release efficiency (reaching 80% after about 100 minutes), which was due to the fact that the hydrogel had a low cross-linked network structure and large micropores, which acted as porous channels and accelerated the release of drugs from the hydrogel. However, the relatively low drug loading (DLC) limited the total release of the drug.
[0071] For the other six GN hydrogels, the drug release efficiency was between 30-55%, and the cumulative release showed a gradually increasing trend before the release time was about 250 minutes. Among them, it was found that the GN-5 hydrogel reached the highest release level of 55.4±0.2% at 255 minutes, and also had the highest DLC and DEE. This is because the expansion of the gel or the contraction of the network helps the diffusion of drug molecules, and the cleavage of the CN bond by ultraviolet light provides an internal network channel for the hydrogel.
[0072] Considering that about half of the curcumin was not released. Considering the physical cross-linking structure and temperature sensitivity of GN hydrogel, the drug release under elevated temperature conditions was further observed. The drug release of GN-5 hydrogel at 45°C and 60°C was further explored. With the increase of temperature, the amount and rate of drug release increased. After culturing for 255min and 200min at 45°C and 60°C, the cumulative release rates of curcumin were 64.6±0.3% and 92.3±0.2%, respectively. Through heating treatment, the second stage release of curcumin was successfully achieved, and periodic drug administration was realized. This achievement was due to the hydrogen bond cross-linking between gelatin and NAGA based entirely on physical effects.
[0073] 7. Curcumin Release Kinetics The drug release data were fitted with kinetic models, including zero-order, first-order, Higuchi and Ritger-Peppas models. The release behavior of curcumin in various GN hydrogels at 37°C was analyzed. The release behavior of curcumin in GN-5 hydrogel was also analyzed at 45°C and 60°C.
[0074] Zero-level kinetic model: ; First-level kinetic model: ; Higuchi model: ; Ritger-Peppas model: ; Among them, M t is the cumulative drug release of curcumin at time t, M ∞ is the total drug loading on the hydrogel, n is the release index, t is the release time, and K is the release rate constant of the corresponding model.
[0075] Test results: Four kinetic models, namely zero-order, first-order, Higuchi and Ritger-Peppas, were used to fit the release behavior of curcumin from Cur@GN hydrogel. According to the model equation shown in the experimental part, the corresponding parameters and regression coefficients R are listed in Table 1. 2 , the fitting diagram is as follows Figure 8 As shown in Figure 2, the drug release behavior is consistent with the Ritger-Peppas model according to the comparison of the four fitting results. 2All are greater than 0.99. In the Ritger - Peppas model, the n - parameter is crucial as it represents the characteristic index of the drug release mechanism. When n ≤ 0.45, Fickian diffusion plays a dominant role; when n ≥ 0.89, matrix relaxation plays a key role; when 0.45 < n < 0.89, Fickian diffusion combines with matrix relaxation to form a combined mechanism. According to the n - values shown in Table 1, the drug release of various Cur@GN hydrogels proceeds through the combination of Fickian diffusion and matrix dissolution. However, it can be seen that the n - value of the GN - 2 hydrogel is the highest, at 0.8, close to the critical value of 0.89, while the n - values of the GN - 7 and GN - 8 hydrogels are the lowest, at 0.51, close to another critical value of 0.45. In addition, with NB the increase in the dosage of NAGA, the n - value shows a regular decreasing trend. In other words, with the participation of more NB NAGA groups, the Fickian diffusion process is more prioritized compared to the matrix relaxation process. Therefore, during the cleavage process of the o-NB groups after chemical bond breakage, a large number of hydrogen bonds formed between NAGA groups will hinder the natural relaxation of the hydrogel. As Figure 8 shown in Figure e and the data of the Cur@GN - 5 hydrogel at 37 °C, 45 °C, and 60 °C in Table 1, as the temperature increases, the n - value gradually increases from 0.54 to 0.57 and 0.64. This is because when the temperature rises, the thermoresponsive hydrogen - bond interaction causes significant dissolution of the hydrogel matrix, so the drug release efficiency of the GN - 5 hydrogel at high temperature is significantly higher than that at low temperature. The fitting results of this kinetic model also confirm that the fully physically enhanced GN hydrogel has temperature - responsive properties.
[0076] According to the aforementioned drug release kinetic analysis results and the drug release curve, the GN - 5 hydrogel may have an optimal distribution during the dynamic processes of matrix relaxation and Fickian diffusion. Under ultraviolet light irradiation, the o-NB groups of the hydrophobic curcumin - loaded NB are rapidly removed, and an appropriate amount of NB NAGA can ensure its rapid release from the hydrogel. At the same time, the breakage of the NAGA chemical bond and the simultaneous formation of single - hydrogen bonds and double - hydrogen bonds cause the internal micropores to contract, constructing a dense cross - linked network. This helps to form a contracted state before swelling and promotes the diffusion of the hydrophobic drug in the adsorbed water as much as possible. Based on this, it further confirms that the photosensitive NB NAGA groups can assist the release behavior and achieve the best release efficiency at an appropriate degree of substitution.
[0077] Table 1 Simulated set parameters derived from different release kinetics
[0078] 8. Thermosensitive properties of GN hydrogels By adding a certain amount of diamide groups into the gelatin macromolecule NB NAGA monomer, designed and synthesized a gelatin-based physically enhanced adhesive hydrogel. The fully physically enhanced GN hydrogel is more sensitive to temperature than the chemically enhanced system. Natural gelatin gels dissolve due to the dissociation of the collagen triple helix structure, resulting in instability at body temperature, which greatly limits their application in the pharmaceutical and medical fields. A GelMA-modified gelatin that can establish chemical cross-linking between protein chains greatly improves the thermal stability of gelatin materials, but also reduces thermal reversibility (Public Document 2: Van Den Bulcke AI, Bogdanov B, De Rooze N, Schacht EH, Cornelissen M, Berghmans H (2000) Structural and rheological properties of methacrylamidemodified gelatin hydrogels. Biomacromolecules 1(1):31-38.). The G′ and G″ of different GN hydrogels decrease with increasing temperature ( Figure 5 a), this phenomenon shows that heating can make the hydrogel gradually become flexible, then semi-solid, and finally free flowing. The intersection of G′ and G″ is the gel-sol transition point of the hydrogel. Obviously, the gel-sol transition temperature of each GN is affected by NB Effect of NAGA content. NB The effect of NAGA content increased the gel-sol transition temperature of GN hydrogels from about 42°C for GN-2 to about 78°C for GN-5. As the temperature increased, the destruction of the physical network intensified, resulting in a significant softening of the hydrogel, which facilitated the removal of the hydrogel in aspects such as clinical wound management. Figure 5 b shows the frequency scan measurement results of GN-5 hydrogel at 25°C and 80°C and the actual photos at the corresponding temperatures. Obviously, at 25°C, G′ far exceeds G″, and its state is a relatively hard solid. At 80°C, G″>G′, and it turns into a flowable liquid. Within the measured temperature range, the Tgel–sol phenomenon of GN-6, GN-7 and GN-8 hydrogels did not occur. This may be because the dynamic decomposition process of the physical network at different temperatures is different, which depends not only on the degree of cross-linking density, but also on the decomposition of the synergistic effect between the diamide structure and the triple helix structure.
[0079] Among the synthesized hydrogels, GN-5 hydrogel has the highest adhesion strength, with a specific value of 106±4.1 kPa (see Figure 4b). Therefore, the adhesion strength of GN-5 hydrogel under different temperature conditions was deeply investigated, and its cyclic adhesion performance was tested. Obviously, thanks to the thermosensitive properties of GN-5 hydrogel, its adhesion strength can be regulated by temperature (see Figure 5 c). As the temperature rises to 35°C, the adhesion strength decreases to 82.1±2.7 kPa; when the temperature continues to rise to 45°C, the adhesion strength decreases significantly to 20.8±2.3 kPa; and at 55°C, the adhesion strength further decreases to 6.9±0.9 kPa. After five rounds of adhesion tests at 25°C and 55°C (see Figure 5 d) The GN-5 hydrogel showed no obvious fatigue or adhesion degradation, indicating its excellent reusability. Therefore, the adhesion and debonding of GN hydrogel can be achieved by adjusting the temperature.
[0080] 9. Self-healing and injectable The strain amplitude sweep test of GN-5 hydrogel at 25°C was performed to evaluate its self-healing ability. Figure 6 As shown in a, G′ and G″ of GN-5 hydrogel reach equilibrium only when the strain is close to 100%, which indicates that it has strong elastic deformation ability. As the strain gradually increases, the G′ value drops sharply, while the G″ value gradually increases. The critical strain point appears at a strain of about 576%, which is the intersection of the G′ and G″ curves. After that, the G′ value is lower than the G″ value, indicating that the hydrogel softens and becomes flowable.
[0081] Next, the rheological behavior under different strain conditions was further explored. When the strain was 1%, the G′ value was greater than the G″ value, which is a characteristic of normal hydrogels. When the strain suddenly increased to 800%, the G′ value dropped sharply from 2900Pa to 200Pa in about 200s, while the G″ value increased from 30Pa to 500Pa, indicating that the state of the hydrogel changed. In order to test its recovery performance, the strain was restored to 1% at 400s. The results showed that the G′ value rose sharply to 2800Pa and the G″ value fell back to 30Pa. Overall, except for slight differences that may be caused by the fact that some hydrogen bonds on the interface were not covered, the others were almost all recovered. In addition, similar changes were observed in the continuous cyclic strain test (1%-800%-1%), indicating that the GN-5 hydrogel has good recoverability.
[0082] The viscosity of GN-5 hydrogel was tested at 25°C. Figure 6 As shown in Figure c, as the shear rate increases, the viscosity gradually decreases, which is a typical shear thinning behavior. This phenomenon is caused by the shear-induced breakage of the dynamic physical network on the GN-5 hydrogel.
[0083] Figure 6 d The self-healing of GN-5 hydrogel is described by a photo. The light yellow disc-shaped GN-5 hydrogel ( Figure 6 d, upper left) into two equal pieces ( Figure 6 d, upper right, and then one of the blocks was stained with rhodamine B solution ( Figure 6 d, lower right). The two hydrogels were then transferred to a mold so that they were in close contact and stored at 40°C for about 20 minutes. After 20 minutes, the two hydrogels were bonded together and could be picked up at one end with tweezers without falling off ( Figure 6 d, lower left). To verify the healing efficiency, the initial hydrogel and the self-healing hydrogel were further subjected to compression strain tests ( Figure 6 e). The healed hydrogel generally maintained its compressive properties. After that, it was further injected into a culture dish filled with water using a syringe under UV light. It can be clearly seen that the GN-5 hydrogel quickly formed and remained in the gel state ( Figure 6 f). Good injectability is the key to the use of bioadhesives in minimally invasive surgery, in which the injectability of bioadhesives is crucial.
[0084] 10. Conclusion In the present invention, the amide group on the lysine residue is successfully used to NB The olefin on the NAGA monomer undergoes a one-step Michael addition reaction to convert the photosensitive bisamide monomer into NB NAGA was grafted onto natural gelatin. By controlling the reaction conditions, a series of GNs with different degrees of substitution (DS) were prepared, with DS ranging from 6.6±1.1% to 77.4±2.2%. Among these GNs, GN-5 hydrogel exhibited the best overall performance with a DS of 41.2±1.3%. Thanks to the UV-light "uncaged" diamide structure and the rearrangement of the inherent helical network of gelatin, the hydrogel can be rapidly formed from a dilute solution within tens of seconds under UV light irradiation. Its mechanical properties were significantly improved, with a final modulus of approximately 3100Pa and a compressive strain of approximately 800kPa. In addition, the photosensitizer o- NB The hydrophobicity of the group gives gelatin the ability to load and release hydrophobic curcumin drugs. More importantly, this completely physical network structure gives the hydrogel the ability to degrade, deform, adhere and self-heal, and can release curcumin as the temperature rises in the subsequent second stage. The results of cytotoxicity experiments further confirmed the biocompatibility. Therefore, the GN hydrogel developed by the present invention shows great application potential in the field of biomedical materials.
[0085] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing an injectable, reversibly adherent, drug-delivery-type physically enhanced gelatin hydrogel, characterized in that: The following steps are involved: (1) Weigh N' -(2-Nitrobenzyl)- N - dissolving acryloyl glycinamide and dimethyl sulfoxide in a light-proof environment to obtain a pre-use solution; (2) Weigh gelatin and ultrapure water to dissolve, and after complete dissolution, adjust the pH to 9 with saturated sodium bicarbonate solution, continue to add ultrapure water and stir thoroughly to obtain a gelatin aqueous solution; (3) In a light-proof environment, slowly drop the pre-used solution into the gelatin aqueous solution for reaction, put the solution after the reaction into an activated dialysis bag for dialysis, and then freeze-dry after the dialysis is completed to obtain a white foamy substance; (4) Under light-proof environment, weigh the white foamy substance and dissolve it in PBS buffer solution. After it is completely dissolved, transfer the resulting precursor solution into a mold and treat it with ultraviolet light to obtain an injectable, reversibly adhesive drug-delivery gelatin hydrogel.
2. The method for preparing the injectable, reversibly adherent, drug-delivery-type physically enhanced gelatin hydrogel according to claim 1, characterized in that: In step (1), N' -(2-Nitrobenzyl)- N -The solid-liquid ratio of acrylyl glycinamide and dimethyl sulfoxide is (4-50): 1 mg / mL; the dissolution temperature is 50°C.
3. The method for preparing the injectable, reversibly adherent, drug-delivery-type physically enhanced gelatin hydrogel according to claim 1, characterized in that: In steps (1)-(2), N' -(2-Nitrobenzyl)- N -The mass ratio of acrylyl glycinamide to gelatin is (0.04-0.5): 1 g / g.
4. The method for preparing the injectable, reversibly adherent, drug-delivery-type physically enhanced gelatin hydrogel according to claim 1, characterized in that: In step (2), the solid-liquid ratio of gelatin to the total amount of ultrapure water is 1:19 g / mL; the dissolution temperature is 50° C.; and the stirring time is 2 h.
5. The method for preparing the injectable, reversibly adherent drug-delivery type physically enhanced gelatin hydrogel according to claim 1, characterized in that: In step (3), the reaction temperature is 50°C, the reaction time is 24 hours, the dialysis time is 72 hours, the freeze-drying time is 24 hours, and the storage temperature of the white foamy substance is -20°C.
6. The method for preparing the injectable, reversibly adherent, drug-delivery-type physically enhanced gelatin hydrogel according to claim 1, characterized in that: In step (3), the dialysis bag is a MWCO 3500 dialysis bag.
7. The method for preparing the injectable, reversibly adherent, drug-delivery-type physically enhanced gelatin hydrogel according to claim 1, characterized in that: In step (4), the concentration of the precursor solution is 10% w / v; and the dissolution temperature is 40°C.
8. The method for preparing the injectable, reversibly adherent, drug-delivery-type physically enhanced gelatin hydrogel according to claim 1, characterized in that: In step (4), the ultraviolet irradiation treatment is performed using a 365 nm ultraviolet lamp at 30 mW / cm 2 Irradiate with the radiation intensity for 5 min.
9. Use of the injectable, reversibly adherent, drug-delivery-type physically enhanced gelatin hydrogel prepared by the preparation method according to any one of claims 1 to 8 in a hydrophobic drug sustained-release carrier.
Citation Information
Patent Citations
Gelatin-based high strength hydrogel and preparation method thereof
CN109206634A
PNAGA reinforced aldehyde hydrazine cross-linked injectable hydrogel and preparation method thereof
CN110092920A
Acryloyl-N-(2-nitrobenzyl) glycine amide photosensitive monomer and preparation method thereof
CN112552204A
Shape memory hydrogel as well as preparation method and application thereof
CN117510755A
Crosslinked gelatin hydrogels
US20140154212A1